A Study on Students’ Perception of Using Movies to Improve English Speaking Skill : (A Descriptive Study at Year-11 of SMA Negeri 2 Mempawah Hilir) - Pratiwi, Della Anugrah; Sudarsono; Sutapa, Yohanes Gatot; Regina; Sumarni (Kirana Publisher (KNPub), 2023)
This research is to identify how the students’ perception of using movie to improve students’ English speaking skill of SMA Negeri 2 Mempawah Hilir. It is a descriptive study and the participants are 60 students of year-11 of SMA Negeri2 Mempawah Hilir. The data were obtained using questionnaires. The data analysis is focused on students’ perception as the main component supporting compelling education and learning. The result of this research were analyzed qualitatively. The findings showed that the students have mostly been positively responded. It can be seen from the results of the questionnaire. For positive response, the students expect it would give them more many educational movies published that can help them supplement their education. Overall, it can be concluded that using movie had been contributed to improve the students’ English speaking skill.